2018
DOI: 10.1177/1073110518782949
|View full text |Cite
|
Sign up to set email alerts
|

The Opioid Crisis in Black Communities

Abstract: While much of the social and political attention surrounding the nationwide opioid epidemic has focused on the dramatic increase in overdose deaths among white, middle-class, suburban and rural users, the impact of the epidemic in Black communities has largely been unrecognized. Though rates of opioid use at the national scale are higher for whites than they are for Blacks, rates of increase in opioid deaths have been rising more steeply among Blacks (43%) than whites (22%) over the last five years. Moreover, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
165
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 242 publications
(166 citation statements)
references
References 43 publications
1
165
0
Order By: Relevance
“…In majority minority cities such as Washington, DC it has been found that upwards of 80% of Opioid deaths are amongst the Black community, a 245 percent increase within a three-year timespan (NPR,2018). Other major cities such as Chicago also have noticed a 56% higher overdose rate in 2015 to 2016 amongst their black communities than their white (James & Jordan, 2018). Taken together, it is clear that racial discrimination is an uncontrollable stressor that can have a harmful impact on behavioral health.…”
mentioning
confidence: 99%
“…In majority minority cities such as Washington, DC it has been found that upwards of 80% of Opioid deaths are amongst the Black community, a 245 percent increase within a three-year timespan (NPR,2018). Other major cities such as Chicago also have noticed a 56% higher overdose rate in 2015 to 2016 amongst their black communities than their white (James & Jordan, 2018). Taken together, it is clear that racial discrimination is an uncontrollable stressor that can have a harmful impact on behavioral health.…”
mentioning
confidence: 99%
“…For nearly 20 years, more than 350,000 Americans with the majority White Americans in the Rust Belt of northern states have died of opioid related drugs (Siemaszko, 2018). James and Jordan (2018) maintained that although the most dramatic increase in opioid-related deaths occurred in White Americans, the opioid epidemic has also greatly affected communities of color.…”
Section: Based On Information From Center For Behavioral Health Statimentioning
confidence: 99%
“…As alleged by Netherland and Hansen (2017), a very different system for responding to the drug use of whites has emerged. According to James and Jordan (2018), more emphasis is being placed on the disease model of substance use disorders, thus saying that individuals who misuse opioids should receive medical treatment. The response to white Americans addiction, differs greatly from the past approach to the crack/cocaine drug use when used mostly by Black Americans.…”
Section: Based On Information From Center For Behavioral Health Statimentioning
confidence: 99%
See 1 more Smart Citation
“…While most efforts have been focused on targeting opioids, there is little information about vulnerable populations at high risk of opioid abuse and death, where and what demographical groups are at higher risk, and what are the drivers boosting the epidemic of opioid overdose deaths in the recent years 12 .…”
mentioning
confidence: 99%